ANALISIS TENTANG PERSEPSI MAHASISWA PRODI PPKN TERHADAP PERAN DAN FUNGSI BADAN PEMBINAAN IDEOLOGI PANCASILA DI FKIP UNIVERSITAS RIAU - Silvia Lusitania Sitinjak; Ahmad Eddison; Supentri Supentri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This research is motivated by a crisis regarding students' knowledge about Pancasila values and threats in the form of radical movements that try to replace the Pancasila ideology with other ideologies and the number of behaviors that do not reflect the noble values of Pancasila. In response to this, President Joko Widodo formed the Pancasila Ideology Development Institute (BPIP) which is regulated in Presidential Decree No. 7 of 2018. The formulation of the problem of this research is how the PPKn study program students' perceptions of the role and function of the Pancasila ideology development body at FKIP, Riau University. This research method is descriptive quantitative. The purpose of this study was to determine how PPKn study program students' perceptions of the role and function of the Pancasila ideology development body in FKIP, Riau University. Data collection techniques are questionnaires (questionnaire), observation, interviews and documentation. The population in this study were 216 students of the PPKn Study Program, 2018, 2019 with a sample size of 45 people. Based on the results of this study, it can be concluded that the perceptions of PPKn study program students on the role and function of the Pancasila Ideology Development Board at FKIP Riau University are in the "Very Good" category with a total of 94.72% of respondents strongly agree plus agree. So it can be concluded that PPKn study program regarding the role and function of the Pancasila Ideology Development Agency in FKIP Riau University is "Very Good".Key Words: Analysis, Perception, Students, Role and Function, BPIP